2021
DOI: 10.4322/2176-1523.20212466
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the applicability of polymeric solutions as cooling fluid in the quenching of low-alloy steels

Abstract: Engineering manufacturing involves the application of different steps to guarantee materials processability and performance in service. This, normally, requires machining, conformation, surface, and heat treatments. A modern concern is related to the process sustainability, the manufacturing capacity to achieve the required properties at low environmental impacts. In this sense, this work evaluated the application of the Polyalkylene Glycol solution (PAG) as a cooling medium of AISI 4140 low alloy steels. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Assim como outros polímeros, o PAG garante uma alta homogeneização na distribuição da fase martensita formada na têmpera e pequena queda no perfil de dureza [13], mas a concentração de polímero na solução é um parâmetro que pode ser alterado buscando uma maior ou menor retirada de…”
Section: /9unclassified
“…Assim como outros polímeros, o PAG garante uma alta homogeneização na distribuição da fase martensita formada na têmpera e pequena queda no perfil de dureza [13], mas a concentração de polímero na solução é um parâmetro que pode ser alterado buscando uma maior ou menor retirada de…”
Section: /9unclassified
“…Our previous research [15][16][17] demonstrates the benefits of applying polymeric solutions in the Heat treatment of low alloy steels. Through the tempering of AISI 4140 steel samples in different cooling media (water, oil, and polyalkylene glycol (PAG) solution), the results demonstrate the advantages of applying PAG, which ensures better homogenization in the distribution of martensite and maintains the hardness profile by eliminating phase steam, and evolution to boiling and convection.…”
Section: Introductionmentioning
confidence: 99%
“…Through the tempering of AISI 4140 steel samples in different cooling media (water, oil, and polyalkylene glycol (PAG) solution), the results demonstrate the advantages of applying PAG, which ensures better homogenization in the distribution of martensite and maintains the hardness profile by eliminating phase steam, and evolution to boiling and convection. In addition, polymeric solutions have the advantage of being biodegradable and producing a more homogeneous heat exchange throughout the quenching process [7,8,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the options for solving it is the development of new compositions of quenching media (QM), which, in addition to the intended purpose, provide manufacturability, environmental friendliness of the heat treatment process and are in an affordable price range. For example, aqueous QMs based on polyalkylene glycols [1][2][3][4][5] have been used for quenching for more than 30 years and ensure product quality, but the price of the polymer and high concentration in the working solution reduce the availability of the product on the world market. Studies of QM based on other water-soluble polymers have shown [6][7][8][9][10][11][12] the possibility of their practical use, however, this complicates the technological maintenance, because due to thermomechanical destruction of macromolecules and a decrease in molecular weight (Mm), the viscosity of the working fluid decreases, which negatively affects the main technological indicators of QM [11][12].…”
Section: Introductionmentioning
confidence: 99%